Sinuciderea - Beca, Elena (Calitatea Vieții, 1992)
The scientific literature offers a global image of the suicide phenomenon and a description of the different ways to approach this topic. Replied on a desk research concerning the suicide size and pattern in Romania, this paper is an argument of considering them as indicators of the quality of life.